(untitled) (KULT_online, 2014)
The editors Judith Schlehe and Evamaria Sandkühler set out to investigate popular religion as a useful conceptual term. The objective is to grasp deinstitutionalized religious lifestyles and ideas as well as reconstructions and reinventions of traditions within local situations and along historical developments in transcultural perspective. In this way, conditions of specific power relationships, discourses, and practices on the ground as well as transnational interconnectedness and global exchange processes are examined. A more comprehensive analysis is achieved through three articles introducing the reader to the topic on a historical-conceptual level. The remaining eight articles are divided by geographical allocation to Southeast Asia and Europe. Rich in empirical material as well as theory-led debate, this volume is interesting for everyone concerned with religion and/or popular culture across disciplines.